ASSOCIATION BETWEEN THE PROTON PUMP INHIBITOR USE AND INCREASED HAZARD OF INTERSTITIAL NEPHRITIS (Journal of Medical & Health Sciences Review, 2025)
Background: Proton pump inhibitors (PPIs), widely used to manage gastric acid-related disorders, have been increasingly linked to renal complications, particularly interstitial nephritis (IN). Acute interstitial nephritis (AIN) is characterized by inflammation in the renal interstitium and can progress to chronic kidney disease if not promptly diagnosed.Objective: To determine the association between PPI use and the incidence of interstitial nephritis among adult patients.Methodology: This case-control study was conducted at Hameed Latif Hospital, Lahore from 10 December 2024 to 31 May 2025. A total of 70 patients (35 cases with interstitial nephritis and 35 controls without) aged 18–70 years were selected using non-probability consecutive sampling. Clinical data, laboratory results, and PPI usage history were recorded using a structured proforma. Data were analyzed using SPSS version 27.Results: PPI use was significantly more frequent among cases than controls. The odds ratio demonstrated a strong association between PPI exposure and interstitial nephritis. After adjusting for age, gender, and comorbidities such as diabetes and hypertension, the association remained statistically significant (p < 0.05).Conclusion:There is a significant association between the use of proton pump inhibitors and the incidence of interstitial nephritis. Caution should be exercised while prescribing PPIs, especially among elderly individuals or those with predisposing factors.